Comparing fecal DNA capture‐recapture to mark‐resight for estimating abundance of mule deer on winter ranges. Issue 2 (20th December 2022) - Stewart, Andi M.; Conner, Mary M.; McKeever, Jane S.; Ellsworth, Alisa; Crowhurst, Rachel S.; Epps, Clinton W.; Stephenson, Thomas R.
Abstract: Monitoring big game populations is necessary for making well‐informed management decisions. In the eastern Sierra Nevada in California, USA, mule deer ( Odocoileus hemionus ) herds have been monitored using traditional mark‐resight methods on winter ranges since the 1990s. Although mark‐resight methods work well for estimating abundance, animal capture for marking is expensive, invasive, and risky. We were motivated to evaluate fecal DNA‐based capture‐recapture for estimating abundance on winter ranges based on the effectiveness of this new technique in other populations in California. This method has been successful for estimating abundance when animals are concentrated around a required resource or pellets are collected from game trails, but it has not been evaluated using randomly selected transects on winter ranges where traditional methods work well. We compared precision (CV) and cost of fecal DNA capture‐recapture surveys to aerial mark‐resight surveys for estimating population abundance. In the Round Valley and Goodale study areas in the eastern Sierra Nevada, we conducted annual aerial mark‐resight surveys and collected fecal pellet samples in Round Valley during winter 2020. We genotyped fecal DNA from pellets to identify unique individuals and sex. Population abundance estimates from aerial mark‐resight surveys were more precise in Round Valley (CV = 6.6%) compared to abundance estimates from fecal DNA capture‐recapture (CV = 20.4%). But based on simulations from Round Valley data, to obtain the same CV (CV = 10%), fecal DNA capture‐recapture was about 63% less expensive than aerial mark‐resight using very high frequency collars and 70% less expensive than aerial mark‐resight using global positioning system collars. In contrast, fecal DNA capture‐recapture did not succeed in the Goodale study area because of weather and logistical constraints. Determining which method is best depends on the situation, but fecal DNA capture‐recapture provides another tool for estimating population size on winter range. We conclude that fecal DNA capture‐recapture is a cost‐effective alternative for estimating abundance of ungulates on winter ranges when weather is not limiting and when researchers can survey an adequate proportion of the study area and collect an adequate number of samples. Abstract : We compared precision (CV) and cost of fecal DNA capture‐recapture surveys to aerial mark‐resight surveys for estimating population abundance. Based on simulations from our data, to obtain the same CV (CV = 10%), fecal DNA capture‐recapture was about 63% less expensive than aerial mark‐resight using VHF collars and 70% less expensive than aerial mark‐resight using GPS collars. We conclude that fecal DNA capture‐recapture is a cost‐effective alternative for estimating abundance of ungulates on winter ranges when weather is not limiting and when researchers can survey an adequate proportion of the study area and collect an adequate number of samples.